Iowa CBC reporting form, Waterloo, December 21, 1985 - Moore, Francis L.et al (1985)
Checklist dated December 21, 1985 compiled by Francis Moore. A list of birds sighted by Moore and five others around Waterloo. A total of 36 species and 4,513 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed